The Development And Evaluation Of A Chinese Cultural Music Module On Chinese Culture Cognition, Learning Motivation And Cross-Cultural Adaptability Among The Freshmen From ‘The Belt And Road’ Countries In China’s Higher Vocational College - Wang, Qiang (2024)
This study developed a Chinese cultural music module to solve the main problems of low level of Chinese culture cognition, learning motivation and cross-cultural adaptability faced by freshmen from ‘the Belt and Road’ countries in Chinese higher vocational colleges.